2018
DOI: 10.1002/pc.25098
|View full text |Cite
|
Sign up to set email alerts
|

Enriched mechanical, thermal, and blood compatibility of single stage electrospun polyurethane nickel oxide nanocomposite for cardiac tissue engineering

Abstract: Electrospinning is a versatile technique for producing nanocomposite in biomedical applications. In this study, polyurethane (PU) cardiac patch loaded with nickel oxide (NiO) was fabricated using electrospinning technique. The morphology study revealed that the PU/NiO nanocomposites exhibited reduced fiber diameter (758 AE 157.10 nm) and pore diameter (868 AE 73.26 nm) compared to the pristine PU (fiber diameter 890 AE 116.91 nm and pore diameter 1064 AE 74.31 nm). The contact angle study indicated the decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Jaganathan et al electrospun polyurethane scaffold added with nickel oxide. The addition of nickel oxide resulted in the enhancement of the surface roughness which correlates with our findings [33]. Parizek et al studied the proliferation of vascular smooth muscle cells in the surface modified polyethylene.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Jaganathan et al electrospun polyurethane scaffold added with nickel oxide. The addition of nickel oxide resulted in the enhancement of the surface roughness which correlates with our findings [33]. Parizek et al studied the proliferation of vascular smooth muscle cells in the surface modified polyethylene.…”
Section: Resultssupporting
confidence: 90%
“…Hence, the fabricated nanocomposites showed highly hydrophobic than the pristine PU. The influence of surface wettability (hydrophobic or hydrophilic) on the cell adhesion and proliferation was equivocal [31,32,33]. It was reported that the surfaces with moderate hydrophilicity would exhibit better cell adherence and proliferation [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When observed under SEM, PU/NiO nano-composite showed a reduction in the diameter of fibers and pores by 14% and 18%, respectively, compared to pure PU. Delayed blood clotting and a lower percentage of hemolytic revealed an improved antithrombogenic nature of PU/NiO nanocomposite, which plays a vital role in the repair of cardiac damage [246].…”
Section: Applicationsmentioning
confidence: 99%
“…Nickel had previously been thought to be dangerous to human health; nevertheless, it was found to be present in serum at about 0.2 μg/L in normal individuals. The toxicity of nickel showed to be dose‐dependent, and now, it has been added to the list of possible materials that could be used for tissue engineering, especially for bone (Jaganathan & Mani, 2019). Nickel alloy has some advantages in comparison to traditional scaffold materials.…”
Section: Applications Of Metal Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%